Encoding Context Determines Risky Choice. (May 2021) - Madan, Christopher R.; Spetch, Marcia L.; Machado, Fernanda M. D. S.; Mason, Alice; Ludvig, Elliot A.
Both memory and choice are influenced by context: Memory is enhanced when encoding and retrieval contexts match, and choice is swayed by available options. Here, we assessed how context influences risky choice in an experience-based task in two main experiments (119 and 98 participants retained, respectively) and two additional experiments reported in the Supplemental Material available online (152 and 106 participants retained, respectively). Within a single session, we created two separate contexts by presenting blocks of trials in distinct backgrounds. Risky choices were context dependent; given the same choice, people chose differently depending on other outcomes experienced in that context. Choices reflected an overweighting of the most extreme outcomes within each local context rather than the global context of all outcomes. When tested in the nontrained context, people chose according to the context at encoding and not retrieval. In subsequent memory tests, people displayed biases specific to distinct contexts: Extreme outcomes from each context were more accessible and judged as more frequent. These results pose a challenge for theories of choice that rely on retrieval as guiding choice.